FAKTOR PENYEBAB MENURUNNYA KEJUJURAN PADA SISWA SEKOLAH DASAR - Patrisia Niwu; Kalista Pota Mau; Melani Jena Pinda; Maikel Teodorus Sabneno (STKIP Subang, 2026)
This study aims to determine the causal factors that influence the decline in honesty in elementary school students. The study used a qualitative approach with interviews, observations, and documentation. Data were obtained through interviews with two fifth-grade teachers and six fifth-grade elementary school students. Observations were conducted during the study by providing observation sheets to teachers and students, and also documentation of observations through school regulations, teacher notes, and also research articles. Data analysis was carried out in two stages: data preparation and thematic analysis. The results of the study indicate that factors that cause the decline in honesty in elementary school students, namely internal factors, such as fear, lack of self-confidence, and students' inability to complete assignments given by teachers, which cause students to cheat. As for factors from the school environment, such as academic pressure, lack of character development, and less than optimal implementation of rules that support honest behavior. As well as family factors, in the form of inconsistent parenting patterns in instilling moral values and minimal communication between parents and children. Some students said that they cheated because they felt lazy to do assignments, did not understand the lesson, or lacked confidence in their learning outcomes when facing exams. This shows that dishonest behavior is not only due to moral issues, but also due to the learning difficulties they face, and also the low self-confidence of these students.